PROFESSIONAL PRACTICES AND PERCEPTIONS OF COMMUNITY PHARMACISTS AND PHARMACY TECHNICIANS TOWARDS THE USE OF HERBAL MEDICINES IN INDONESIA - Mizranita, Vinci; Sakinatun Nisa, Fauziyyah (Jurnal Jamu Kusuma, 2024)
This study examines the perceptions of community pharmacists and pharmacy technicians regarding the use of herbal medicines practice in Indonesia. Given the rich biodiversity and traditional medicinal practices in Indonesia, herbal medicines play a significant role in healthcare. This study aims to examine the role of pharmacists and pharmacy technicians in advising patients on herbal medicines, focusing on their knowledge, scope, and practices. A cross-sectional survey was conducted among pharmacists and pharmacy technicians in Surakarta, Indonesia, who attended Indonesian Pharmacists Association (IAI) and Indonesian Pharmacy Technicians Association (PAFI) seminars. A total of 123 pharmacists and 121 pharmacy technicians participated in the study. The results indicate that pharmacy technicians are more involved in managing simple common ailments such as acne (93.4%) and cough and cold symptoms (90.1%) compared to pharmacists, who are more involved in treating conditions like acute pain (72.4%) and diarrhoea (58.5%). This study also show a significant shift in referral patterns when symptoms do not improve, with pharmacy technicians referring patients to pharmacists 89.3% of the time. This study highlights the critical role of pharmacy technicians in the initial management of symptoms and underscores the importance of collaboration between pharmacists and pharmacy technicians to ensure optimal patient outcomes. The findings suggest areas for further training and protocol development to enhance the efficiency and effectiveness of pharmacy services in Indonesia.